Pemberian Wasiat Wajibah pada Ahli Waris Non-Muslim Perspektif Hukum Progresif - Herlina Nur Afida (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Arresting heirs is crucial because the relationship between humans who have died requires management from their families through inheritance or wills. In Indonesia there has been a dynamic of progress related to the issue of non-Muslim inheritance. Through progressive law it can be seen that statutory regulations have limitations, so that the need for human participation in progressive law. The legal vacuum in Indonesia regarding the inheritance of different religions requires judges as state officials to innovate in order to adapt to the times with the complexities of Indonesian society. This paper aims to analyze the correlation of progressive law in presenting obligatory wills to non-Muslim heirs. This research is a library research with a normative approach. From the results of the study found the implementation of several progressive legal concepts that are aligned with the granting of obligatory wills for non-Muslim heirs. The expansion of obligatory will arrangements in Indonesia can be seen from the MUI Fatwa regarding heirs of different religions or non-Muslims and variations in the results of the Supreme Court's decision regarding the arrangement of obligatory wills. The renewal of the rules regarding the obligatory will is a form of implementation of progressive legal values. The Supreme Court in carrying out its decision regarding the application of the obligatory will is guided by justice and humanity which is in line with the nature of progressive law which has the mission of guiding people towards prosperity and happiness.